A global review of socioeconomic and environmental impacts of ants reveals new insights for risk assessment. Issue 4 (31st March 2022) - Gruber, Monica A. M.; Santoro, Davide; Cooling, Meghan; Lester, Philip J.; Hoffmann, Benjamin D.; Boser, Christina; Lach, Lori
Abstract: Risk assessments are fundamental to invasive species management and are underpinned by comprehensive characterization of invasive species impacts. Our understanding of the impacts of invasive species is growing constantly, and several recently developed frameworks offer the opportunity to systematically categorize environmental and socioeconomic impacts of invasive species. Invasive ants are among the most widespread and damaging invaders. Although a handful of species receives most of the policy attention, nearly 200 species have established outside their native range. Here, we provide a global, comprehensive assessment of the impacts of ants and propose a priority list of risk species. We used the Socioeconomic Impact Classification for Alien Taxa (SEICAT), Environmental Impact Classification for Alien Taxa (EICAT) and Generic Impact Scoring System (GISS) to analyze 642 unique sources for 100 named species. Different methodologies provided generally consistent results. The most frequently identified socioeconomic impacts were to human health. Environmental impacts were primarily on animal and plant populations, with the most common mechanisms being predation and competition. Species recognized as harmful nearly 20 years ago featured prominently, including Wasmannia auropunctata (little fire ant, electric ant), Solenopsis invicta (red imported fire ant), Anoplolepis gracilipes (yellow crazy ant), and Pheidole megacephala (African big‐headed ant). All these species except W. auropunctata have been implicated in local extinctions of native species. Although our assessments affirmed that the most serious impacts have been driven by a small number of species, our results also highlighted a substantial number of less well publicized species that have had major environmental impacts and may currently be overlooked when prioritizing prevention efforts. Several of these species were ranked as high or higher than some of the previously recognized "usual suspects, " most notably Nylanderia fulva (tawny crazy ant). We compared and combined our assessments with trait‐based profiles and other lists to propose a consensus set of 31 priority species. Ever‐increasing global trade contributes to growing rates of species introductions. The integrated approaches we used can contribute to robust, holistic risk assessments for many taxa entrained in these pathways.